2017
DOI: 10.1002/2016jd025224
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional leader development in a preexisting channel as observed in rocket‐triggered lightning flashes

Abstract: Two cases of bidirectional leader, starting almost immediately below a decaying dart or dart‐stepped leader which terminated before reaching the ground, were identified, for the first time, in rocket‐triggered lightning flashes based on high‐speed video, electric field changes, and channel base current, indicating that a bidirectional leader can be excited by a decayed dart leader and propagate in a preexisting discharge channel. The positive end of the bidirectional leader moved upward along the terminated do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 31 publications
8
48
1
Order By: Relevance
“…Therefore, the propagation speeds of the upward positive leader shown in Figure are ~1–2 orders of magnitude larger than traditional upward positive leaders in triggered lightning (Hill et al, ; Jiang et al, ). The observed speed for the upward positive leader is similar to the upward positive leader in bidirectional leaders reported by Jiang et al () and Qie et al (). The higher speed is due to the fact that all these positive leaders propagated in a preexisting discharge channel.…”
Section: Characteristics Of the P1 Discharge Processsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the propagation speeds of the upward positive leader shown in Figure are ~1–2 orders of magnitude larger than traditional upward positive leaders in triggered lightning (Hill et al, ; Jiang et al, ). The observed speed for the upward positive leader is similar to the upward positive leader in bidirectional leaders reported by Jiang et al () and Qie et al (). The higher speed is due to the fact that all these positive leaders propagated in a preexisting discharge channel.…”
Section: Characteristics Of the P1 Discharge Processsupporting
confidence: 88%
“…However, we noticed some differences between the positive leader and those described in the above mentioned literatures. There were downward propagating dart leaders before bidirectional leaders' initiation in both Jiang et al (2014) and Qie et al (2017), while there was no downward negative leader observed by optical and electrical instruments before the upward discharge reported here.…”
Section: 1029/2018gl078548contrasting
confidence: 50%
“…Based on our high‐speed video records of the RLs in this flash and the RL images found in the literatures (e.g., Mazur et al, ; Qie et al, ), we believe that all the RLs were bidirectional, although sometimes only one extending end could be detectable. The negative end of each bidirectional DL extended along one of the decayed branches of the flash‐initiating UPL, attached to the top of the Canton Tower, and initiated a return stroke.…”
Section: Discussion and Summarysupporting
confidence: 61%
“…Zhu et al () argued that RLs were generated in the remnants of either positive or negative leader channel. Qie et al () reported that the positive end of a bidirectional RL retrograded along the previous negative leader channel in a triggered lightning flash. The high‐speed video observations reviewed above confirm that RLs belong to the family of bidirectional leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Bidirectional leaders have also been observed to occur following termination of failed negative dart leaders in both tower initiated lightning (Jiang, Wu, et al, ) and rocket‐triggered lightning (Qie et al, ). Following termination of the dart leader, the bidirectional leaders in both cases initiated at the termination point within one or two frames (10 μs per frame in the former case and 40 μs per frame in the later).…”
Section: Introductionmentioning
confidence: 99%